German Health Update: New data for Germany and Europe - Anke-Christine Saß; Cornelia Lange; Jonas D. Finger; Jennifer Allen; Sabine Born; Jens Hoebel; Ronny Kuhnert; Stephan Müters; Jürgen Thelen; Patrick Schmich; Marike Varga; Elena von der Lippe; et al. (Journal of Health Monitoring, 2017)
GEDA 2014/2015-EHIS is an up-to-date health survey of the adult population undertaken within the framework of the Robert Koch Institute’s (RKI) health monitoring system. It uses the EHIS (European Health Interview Survey) Wave 2 questionnaire and includes four modules covering health status, health care, health determinants, and socio-economic variables. Data on nationally relevant issues is also collected. The study employs a mixed-mode design, using both online and paper-based questionnaires to gather data from 24,016 people aged 18 and above: the response rate was 26.9%. The Statistical Office of the European Union (Eurostat) provides prepared data from 28 European Union (EU) member states (plus Norway and Iceland) on the Eurostat website. National analyses for Germany are published as Fact sheets on health reporting in the Journal of Health Monitoring.